The Influence of Risk Management on the Success of Entrepreneurial Businesses (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a vital pillar of the Indonesian economy, contributing 61% to GDP and employing 97% of the workforce. Despite their importance, MSMEs face a high failure rate of 78–80%, with financial management problems accounting for 82% of failures. This study aims to analyze and prove the influence of risk management on the success of entrepreneurial efforts in MSMEs, while also measuring its contribution in explaining variations in business success. Using a quantitative approach with a survey method, the research involved 100 purposively selected respondents who met criteria of operating for at least two years and employing at least one worker. Data analysis included validity and reliability tests, classical assumption tests, simple linear regression, t-test, and coefficient of determination (R²). Results confirmed that all instruments were valid and reliable, with data meeting normality and heteroscedasticity assumptions. Regression analysis produced the equation Y = 5.428 + 0.724X, showing that risk management positively influences business success. The t-test confirmed significance, while R² = 0.403 indicated that risk management explains 40.3% of success variation. The findings conclude that effective risk management significantly enhances MSME sustainability and entrepreneurial success.